2014
DOI: 10.3310/pgfar02060
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of tools and an intervention to improve patient- and carer-centred outcomes in Longer-Term Stroke care and exploration of adjustment post stroke: the LoTS care research programme

Abstract: This report should be referenced as follows: Programme Grants for Applied ResearchISSN 2050-4322 (Print) ISSN 2050-4330 (Online) This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/).Editorial contact: nihredit@southampton.ac.ukThe full PGfAR archive is freely available to view online at www.journalslibrary.nihr.ac.uk/pgfar. Print-on-demand copies can be purchased from the report pages of the NIHR Journals Library website: ww… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 127 publications
(137 reference statements)
1
13
0
Order By: Relevance
“…In this study, we adopted a longitudinal, grounded theory approach (Charmaz, 2006) to explore poststroke trajectories and the factors that were understood to shape them. This study was part of a larger study), which aimed to improve outcomes after stroke by addressing the longer-term needs of community-dwelling stroke survivors and their carers in the United Kingdom (Forster et al, 2014).…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…In this study, we adopted a longitudinal, grounded theory approach (Charmaz, 2006) to explore poststroke trajectories and the factors that were understood to shape them. This study was part of a larger study), which aimed to improve outcomes after stroke by addressing the longer-term needs of community-dwelling stroke survivors and their carers in the United Kingdom (Forster et al, 2014).…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Impaired functional health, higher financial income, younger age, emotional distress [8], pre-stroke dependency [7], living arrangement, social circumstances [7] and access to a physician [6] have been associated with the use of healthcare services after stroke. Stroke survivors living at home have reported unmet needs in several domains, including mobility, mood, communication, health provision after discharge and managing stroke-related problems [13, 14]. These factors could plausibly affect healthcare utilization after stroke but their association has never been established.…”
Section: Introductionmentioning
confidence: 99%
“…Other adjustments will be needed as the patient adapts to a new way of functioning post-trauma (Forster et al, 2014). For example, Forster et al (2014) identified four possible post-stroke patient outcomes: (a) disruption, adjustment, and acceptance; (b) cycles of disruption, adjustment, and acceptance; (c) disruption without adjustment and acceptance; and (d) continuing ongoing decline. The patient may need, and benefit from, continued therapy and/ or counseling.…”
Section: Resultsmentioning
confidence: 99%